The Oenological Potential of Hanseniaspora uvarum in Simultaneous and Sequential Co-fermentation with Saccharomyces cerevisiae for Industrial Wine Production - Tristezza, Mariana; Tufariello, Maria; Capozzi, Vittorio; Spano, Giuseppe; Mita, Giovanni; Grieco, Francesco (Frontiers in Microbiology, 2016)
In oenology, the utilization of mixed starter cultures composed by Saccharomyces and non-Saccharomyces yeasts is an approach of growing importance for winemakers in order to enhance sensory quality and complexity of the final product without compromising the general quality and safety of the oenological products. In fact, several non-Saccharomyces yeasts are already commercialized as oenological starter cultures to be used in combination with Saccharomyces cerevisiae, while several others are the subject of various studies to evaluate their application. Our aim, in this study was to assess, for the first time, the oenological potential of H. uvarum in mixed cultures (co-inoculation) and sequential inoculation with S. cerevisiae for industrial wine production. Three previously characterized H. uvarum strains were separately used as multi-starter together with an autochthonous S. cerevisiae starter culture in lab-scale micro-vinification trials. On the basis of microbial development, fermentation kinetics and secondary compounds formation, the strain H. uvarum ITEM8795 was further selected and it was co- and sequentially inoculated, jointly with the S. cerevisiae starter, in a pilot scale wine production. The fermentation course and the quality of final product indicated that the co-inoculation was the better performing modality of inoculum. The above results were finally validated by performing an industrial scale vinification The mixed starter was able to successfully dominate the different stages of the fermentation process and the H. uvarum strain ITEM8795 contributed to increasing the wine organoleptic quality and to simultaneously reduce the volatile acidity. At the best of our knowledge, the present report is the first study regarding the utilization of a selected H. uvarum strain in multi-starter inoculation with S. cerevisiae for the industrial production of a wine. In addition, we demonstrated, at an industrial scale, the importance of non-Saccharomyces in the design of tailored starter cultures for typical wines.